Improvement in open circuit voltage of n‐ZnO/p‐Si solar cell by using amorphous‐ZnO at the interface. (7th June 2017) - Hussain, Babar
Abstract: Several research groups are currently working on n‐ZnO/p‐Si heterojunction solar cell, and recently, Pietruszka et al [Sol. Energ. Mat. Sol. Cells 147 (2016) 164‐170] has reported the highest efficiency of 7.1% for this structure. The main challenge is to enhance the open circuit voltage up to theoretically predicted value of >0.6 V. This paper reports >20% improvement in open circuit voltage of n‐ZnO/p‐Si solar cell by depositing amorphous‐ZnO at the interface at room temperature that possibly improves the passivation and/or avoids oxide formation at the interface during ZnO deposition. Two other materials, aluminum nitride and amorphous‐Si, have also been used as buffer layers to evaluate their effect on suppression of interface states. Furthermore, additional advantage of ZnO as an antireflector has been experimentally verified for different thicknesses of ZnO film. Abstract : This paper presents >20% improvement in open circuit voltage of n‐ZnO/p‐Si solar cell by depositing amorphous‐ZnO at the interface at room temperature that possibly improves the passivation and/or avoids oxide formation at the interface during ZnO deposition. Two other materials, aluminum nitride and amorphous‐Si, have also been used as buffer layers to evaluate their effect on suppression of interface states. Furthermore, additional advantage of ZnO as an antireflector has been experimentally verified for different thicknesses of ZnO film.